Analysis of statistical variability activities in secondary education textbooks: a study from an international proposal standpoint - Rodríguez-Alveal, Francisco; Díaz-Levicoy, Danilo; Vásquez, Claudia (Uniciencia, 2021)
The purpose of this paper is to analyze variability activities in secondary education textbooks, which are provided free of charge by the Chilean Ministry of Education, in accordance with the Guidelines for Assessment and Instruction in Statistics Education endorsed by the American Statistical Association and the Common Core State Standards in Mathematics. A qualitative methodology is followed, using content analysis as a method. Sampling was intentional and included eight textbooks of secondary education (freshman, sophomore, junior, and senior), which are in accordance with the current math curriculum in Chile. Results show that, in general, these textbooks do not use real data and do not mention the types of variability, whether natural, induced, or sample variability, to summarize information. In addition, contents are frequently approached in a procedural manner, which restricts teaching to using formulas and, in specific cases, to clarifying certain notations. There is no pedagogical use of computational tools like Excel or GeoGebra. The study evidenced textbook flaws to teach variability, including a lack of clear definitions and their role in statistics. Therefore, teachers should complement what has been indicated in the textbook with new readings and scientific articles on these topics, such as the introduction of appropriate methodologies to teaching statistics and probability, teaching through projects, and case studies with problematic situations in which this concept plays a fundamental role in the decision making.